The acute phase response in children with mild and severe malaria in Papua New Guinea - O'Donnell, A.; Fowkes, F.; Allen, S.; Imrie, H.; Alpers, Michael Philip; Weatherall, D.; Day, K. (Elsevier Ltd, 2009)
The production of acute phase proteins during infection is an important part of innate immunity and limits inflammation. However, little is known of the acute phase response in malaria. We measured acute phase proteins in plasma in children attending clinics and admitted to hospital with acute malaria in Papua New Guinea. Plasma ferritin concentration increased progressively with disease severity with markedly elevated levels in the most severely ill children. Plasma ferritin was >500 ng/ml in 7/99 (7.1%) outpatients with uncomplicated malaria, 22/100 (22.0%) hospital non-severe cases, 64/175 (36.6%) severe malaria cases who survived and 7/9 (77.8%) severe malaria deaths (P < 0.001). The greatest concentration of ferritin (3561 ng/ml) was observed in a child who died. By contrast, C-reactive protein concentration was markedly increased in 153 children with uncomplicated malaria [median 203 (interquartile range 51-365) µg/ml] but, surprisingly, was only moderately increased in 135 children with one or more severe manifestations of malaria [47 (17-97) µg/ml; P < 0.001] and in 6 children who died [41 (22-280) µg/ml]. Excessive free-radical damage resulting from a combination of iron-induced oxidant stress and reduced levels of C-reactive protein may be an important pathological mechanism in severe malaria and amenable to therapeutic intervention. © 2009 Royal Society of Tropical Medicine and Hygiene.